Nanotechnology and Dental Implants - Lavenus, Sandrine; Louarn, Guy; Layrolle, Pierre (International Journal of Biomaterials, 2010)
The long-term clinical success of dental implants is related to their early osseointegration. This paper reviews the different steps of the interactions between biological fluids, cells, tissues, and surfaces of implants. Immediately following implantation, implants are in contact with proteins and platelets from blood. The differentiation of mesenchymal stem cells will then condition the peri-implant tissue healing. Direct bone-to-implant contact is desired for a biomechanical anchoring of implants to bone rather than fibrous tissue encapsulation. Surfaces properties such as chemistry and roughness play a determinant role in these biological interactions. Physicochemical features in the nanometer range may ultimately control the adsorption of proteins as well as the adhesion and differentiation of cells. Nanotechnologies are increasingly used for surface modifications of dental implants. Another approach to enhance osseointegration is the application of thin calcium phosphate (CaP) coatings. Bioactive CaP nanocrystals deposited on titanium implants are resorbable and stimulate bone apposition and healing. Future nanometer-controlled surfaces may ultimately direct the nature of peri-implant tissues and improve their clinical success rate.